Kebijakan Restorasi Bantuan Militer Amerika Serikat ke Mesir Tahun 2014-2015 - Adristy, Tjokorda Istri; Wiranata, I Made Anom; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
United States has decided to cut off military aid to Egypt in 2013. The decision was made due to Egypt’s political unstably that disgrace democratic and human rights values. Despite the fact that Egypt’s domestic situation remained unstable, United States immediately decided to restore the aforementioned military aid to Egypt in 2014-2015. Reasons behind United States’ military aid restoration in 2014-2015 will be explained by applying Neoclassical Realism theory in this research. Based on the applied theory, some findings appeared that the policy to restore military aid are dependent on two reasons. First, systemic stimuli in form of threats arise in international structure. Second, domestic factors such as leader, domestic institution, state-society relations, and strategic culture are the basis of United States to set a policy to counter the systemic stimuli. This research applies qualitative descriptive method.   Keywords: United States of America, military aid, aid restoration policy, Neoclassical Realism